Modeling Consumer Willingness to Consider Electric Motorcycles in Indonesia: A System Dynamics Approach - Ahmad Rafi Adnanta; Roni Zakaria Raung; Wahyudi Sutopo; Ihwan Susila (Jurnal Optimasi Sistem Industri, 2025)
Sustainable transport plays a key role in the fight against climate change, particularly in developing countries where reliance on conventional vehicles is high. Motorcycles account for the majority of the fleet of motor vehicles in Indonesia and contribute significantly to emissions. In order to achieve its Paris target of a 29 percent reduction of carbon emissions, the government is encouraging electric cars with various incentives. This study develops a willingness to consider (WTC) model for electric motorcycles in Indonesia based on the powertrain technology transition market agent model (PTTMAM) and utilizes Vensim software to simulate outcomes. The WTC model is built on the assumption that consumers' willingness to consider electric motorcycles is influenced by factors such as costs, marketing, and exposures. The system dynamics model consists of four modules: the conventional motorcycle, the electric motorcycle, the marketing module, and the willingness to consider module. The simulation results show an increasing trend in consumers’ willingness to consider electric motorcycles from 2017-2035, with the WTC value reaching 0.3209 in 2035. While this indicates a positive shift toward greater consumer interest in electric motorcycles, the growth remains modest and slow, reflecting the challenges of widespread adoption. Additionally, this study evaluates three government incentive and subsidy policy scenarios. The scenario results indicate that government subsidies and incentives can increase the consumers’ willingness to consider electric motorcycles in Indonesia, thereby increasing their market share. Among the scenarios, the purchase price subsidy is the most effective, as it directly reduces the financial barrier, encouraging more consumers to make the switch to electric motorcycles.